Evaluation of choroidal lesions with swept-source optical coherence tomography. Issue 1 (31st March 2018) - Ung, Cindy; Laíns, Inês; Silverman, Rebecca F; Woods, Russell; Lane, Anne Marie; Papakostas, Thanos D; Husain, Deeba; Miller, Joan W; Gragoudas, Evangelos S; Kim, Ivana K; Miller, John B
Abstract : Aims: The aim of our study was to image choroidal lesions with swept-source optical coherence tomography (SS-OCT) and to identify the morphological characteristics associated with optimal visualisation. Methods: This was a prospective, cross-sectional study. Patients with choroidal melanocytic lesions <3 mm in thickness on B-scan ultrasonography were recruited. All participants underwent SS-OCT. On SS-OCT we evaluated qualitative (eg, lesion outline, detection of scleral-choroidal interface and quality of the image) and quantitative (measurement of maximum lesion thickness and the largest basal diameter) parameters. Probability of optimal image quality was examined using ordered logistic regression models. The main outcome measure was quality of the choroidal lesion images on SS-OCT, defined as: optimal, suboptimal or poor. Results: We included 85 choroidal lesions of 82 patients. There were 24 choroidal lesions (29%) for which image quality was classified as optimal, 31 lesions (37%) as suboptimal and 30 lesions (36%) as poor. The factors associated with optimal image quality were distance closer to the fovea (OR 0.76, p<0.001), posterior pole location (OR 3.87, p=0.05), lower ultrasonography thickness (OR 0.44, p=0.04), lighter lesion pigmentation (OR 0.12, p=0.003) and smaller lesion diameter (OR 0.73, p<0.001). In the multivariable analysis, closer distance to the fovea (OR 0.81, p=0.005), lighter lesion pigmentation (OR 0.11, p=0.01) and smaller lesion diameter (OR 0.76, p=0.006) remained statistically significant. Conclusion: SS-OCT is useful in imaging most choroidal melanocytic lesions. Image quality is best when the choroidal lesion is closer to the fovea, has a smaller diameter and a lighter choroidal pigmentation.